Correlation between Pregnancy Anemia and Nutritional Status of Pregnant Women to the Case of Toddlers 2-5 Years Old with Stunting - Aini, Qurrotu; Mufarika, Mufarika; Aini, Nurieta (Kirana Publisher (KNPub), 2022)
Stunting is a nutritional issue that has persisted for a long enough time to affect children who are shorter or lower than the average for their age in terms of height. The case control method is being used in this retrospective research design. the dependent variable of stunting and the independent variables of gestational anemia and pregnant women's nutritional condition. Mothers of toddlers between the ages of 2 and 5 make up the demographic. A case group of 25 people and a control group of 50 people were created from the sample. MCH books and observation sheets are both used in this study. Chi-square test and Odd Ratio test analysis Using the findings of Chi-square statistical tests on the variable anemia of pregnancy, Given that it has a value of 0.000, 0.05, or 6.682 (95% CI: 2.239–19.939), it is possible to draw the conclusion that anemia during pregnancy and stunting in toddlers between the ages of 2 and 5 have a causal link. With a confidence interval of 2.239-19.939, mothers who have a history of anemia during pregnancy run a 6.682-times greater chance of having children who are stunted. It was determined that there was a relationship between the nutritional status of pregnant women and the incidence of stunting in toddlers 2–5 years old based on the statistical test results for the variable nutritional status of pregnant women using Chi-square, which showed a value of :0.016 :0.05 OR 3.58 (95% CI; 1.228–10.431). With a confidence interval of, moms who have a history of poor nutrition are at an increased risk of 3.58 times having toddlers who are stunted. 228-10.431 . ANC K4 . It is hoped that health professionals can collaborate with community members and cadres to empower people in order to stop stunting.